Análisis florístico de dos áreas con bosque mesófilo de montaña en el estado de Hidalgo, México: Eloxochitlán y Tlahuelompa - Alcántara Ayala, Othón; Luna Vega, Isolda (Instituto de Ecología, A.C., 2001)
The cloud forests of Eloxochitlán and Tlahuelompa represent two fragments with different floristic composition of the Hidalgo State, México, in the Huasteca region of the Sierra Madre Oriental. In the arboreal vegetation three vertical strata can be distinguished: high (20-30 or even 40 m), medium (8-20 m), and lower (2-8 m). A floristic list of vascular plants of both areas constituted by 394 species, 266 genera, and 110 families is presented. An analysis of the current distribution of the genera reveals that many of the genera are distributed exclusively in America, usually those of the understory (93 genera, 35%); most genera of the canopy trees are distributed mainly in the Northern Hemisphere (25 genera, 9.4%). The areas with Fagus grandifolia ssp. mexicana in the state of Hidalgo are suggested as reserve areas due to the relictual and endemic character of this taxon.